KANDUNGAN SENYAWA KIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH ALPUKAT (Persea americana P.Mill) TERHADAP BAKTERI Vibrio alginolyticus - Ernawati .; Kumala Sari (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Vibrio alginolyticus is one of the primary pathogenic bacteria that attack the grouper fish. The avocado peel as a natural antibacterial can be used to prevent from the vibrio bacteria attack. The aims of this research study were to find out the chemical compound content of avocado peel extract as an antibacterial and to observe its activity in inhibiting the growth of Vibrio alginolyticus bacteria. The diffusion method through the observation of transparent zones in testing the antibacterial activity of extract of avocado peel was used in this study. The treatments tested were different concentration of avocado peel extract i.e16 mg/ml, 32 mg/ml, 62.5 mg/ml, 125 mg/ml, 125 mg/ml, and 250 mg/ml. The results of the antibacterial activity test using paper disk showed tha tthe largest diameter of transparent zone is 11 mm for 250 mg/ml extract concentration and is classified as the weak growth of response type. In conclusion, the extract of avocado peel that contain anti bacterial compound i.e. flavonoid, saponin, and alkaloid, have an inhibition properties or bacteriostatic on the growth of Vibrio alginolyticus bacteria.